Challenges to the implementation of International Health Regulations (2005) on Preventing Infectious Diseases: experience from Julius Nyerere International Airport, Tanzania - Edith Bakari; Gasto Frumence (Taylor & Francis Group, 2013)
Background: The International Health Regulations (IHR) (2005) is a legal instrument binding all World Health Organization (WHO) member States. It aims to prevent and control public health emergencies of international concern. Country points of entry (POEs) have been identified as potential areas for effective interventions to prevent the transmission of infectious diseases across borders. The agreement postulates that member states will strengthen core capacities detailed in the IHR (2005), including those specified for the POE. This study intended to assess the challenges faced in implementing the IHR (2005) requirements at Julius Nyerere International Airport (JNIA), Dar es Salaam. Design: A cross-sectional, descriptive study, employing qualitative methods, was conducted at the Ministry of Health and Social Welfare (MoHSW), WHO, and JNIA. In-depth interviews, focus group discussions (FGDs) and documentary reviews were used to obtain relevant information. Respondents were purposively enrolled into the study. Thematic analysis was used to generate study findings. Results: Several challenges that hamper implementation of the IHR (2005) were identified: ()1 none of the 42 Tanzanian POEs have been specifically designated to implement IHR (2005). (2) Implementation of the IHR (2005) at the POE was complicated as it falls under various uncoordinated government departments. Although there were clear communication channels at JNIA that enhanced reliable risk communication, the airport lacked isolated rooms specific for emergence preparedness and response to public health events. Conclusions: JNIA is yet to develop adequate core capacities required for implementation of the IHR (2005). There is a need for policy managers to designate JNIA to implement IHR (2005) and ensure that public health policies, legislations, guidelines, and practice at POE are harmonized to improve international travel and trade. Policy makers and implementers should also ensure that implementation of the IHR (2005) follow the policy implementation framework, particularly the contextual interaction theory which calls for the availability of adequate resources (inputs) and well-organized process for the successful implementation of the policy.